2023
DOI: 10.1002/ange.202217225
|View full text |Cite
|
Sign up to set email alerts
|

A Pair of Interconverting Cages Formed from Achiral Precursors Spontaneously Resolve into Homochiral Conformers

Abstract: Without chiral induction the emergence of homochirality from achiral molecules is rather serendipitous, as the rationale is somewhat ambiguous. We herein provide a plausible solution. From achiral precursors are formed a pair of interconverting cage conformers that exhibit a C 3 -axis as the only symmetry element. When their interconversion is impeded with intramolecular H-bonding, each conformer self-sorts into a homochiral crystal, which is driven by a helical network of multivalent intermolecular interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Each Around the crystallographic b-axis, each FPy molecule rotates by 180° with respect to another, so that they are packed in a head-to-tail manner along the helical trajectory, forming a chiral supramolecular 21-helix, in line with our previously proposed strategy of "go with the flow". 18 The helices are extended on the ac plane to afford the chiral polar monoclinic crystalline phase (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each Around the crystallographic b-axis, each FPy molecule rotates by 180° with respect to another, so that they are packed in a head-to-tail manner along the helical trajectory, forming a chiral supramolecular 21-helix, in line with our previously proposed strategy of "go with the flow". 18 The helices are extended on the ac plane to afford the chiral polar monoclinic crystalline phase (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…Given over 60% of noncentrosymmetric crystals (41/65 Sohncke space groups) exhibit screw symmetry, we recently proposed a strategy that favors spontaneous chiral resolution of racemic molecules, which we termed "go with the flow": 18 When rational molecular design facilitates the exerting of multivalent intermolecular interactions along the helical trajectory of screw symmetry of the molecular packing, the racemates could experience narcissistic self-sorting during crystallization, leading to the formation of homochiral conglomerates. We also applied this strategy to a series of achiral D-A molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, chirality switching employing organic compounds involving molecular asymmetry can be translated into digital information without changing its chemical property except the absolute configuration. [6][7][8][9][10] We have reported that the ring-closing metathesis (RCM) of (hetero)biaryl bearing a terminal alkenyl substituent at each aromatic ring undergoes a cyclization reaction and the thus formed product indicates molecular asymmetry. We have been studying the thus obtained cyclized product, which we call such a kind of chirality as the winding vine-shaped molecular asymmetry.…”
Section: Introductionmentioning
confidence: 99%